ENGAGEMENT GURU UNTUK PENINGKATAN KREATIVITAS DI MTS KOTA MADIUN DENGAN ANALISIS SITOREM - Rais, Sasli; Ropiqi, Moh. Abdul (LPPM Universitas Islam 45, 2024)
The research aims to find strategies and ways to improve creativity, by testing the strength of the relationship between teacher engagement and creativity. The study uses a quantitative approach with a correlational research method, with data collection through surveys. Data analysis techniques, using correlational analysis and SITOREM analysis. The research sample was 114 teachers, from a population of 160 teachers at MTs Kota Madiun. Determination of the sample using the Taro Yamane formula, selected using proportional random sampling techniques. The results of the study indicate that there is a positive and significant relationship between teacher engagement and creativity. This means that strengthening teacher engagement will be able to increase their creativity. The results of the SITOREM analysis show that there are indicators of teacher engagement that are a priority to be improved, namely: the job is important, interest in organizational goals, having competence, opportunities for self-development, and high performance for self-esteem. Indicators that need to be maintained/developed are actively participating in their work.